Silk Implants for Localized Small Molecule Drug Delivery to Treat Traumatic Brain Injury. - Rao, Varuna. (2017)
Abstract: Traumatic brain injury (TBI) is the leading cause of death and disability worldwide. Resulting from blunt or penetrating forces to the head, TBI can affect any population of individuals. Following primary injury, or the initial mechanical insult, brain tissue undergoes secondary injury, notably necroptosis, or controlled tissue death. Administration of necroptosis inhibitors and other small molecules to alter the signaling cascade of tissue death has the potential to minimize the harmful short-term and long-term effects of secondary injury. Unfortunately, pharmaceuticals designed to target the brain have one major obstacle that medications to other sites of the body do not encounter - the blood barrier (BBB), a highly selective semi-permeable endothelial cell capillary network that protects the brain from toxic substances. The few drugs that successfully cross the BBB are only able to do so after reaching high systemic concentrations, adversely affecting the rest of the body. Invasive approaches by means of drug-eluting biodegradable polymer implants show greater potential for localized delivery. Among the most successful natural polymers is silk fibroin which boasts several qualities such as biocompatibility, biodegradability, and extraordinary tunability of chemical and mechanical properties, making it a very useful biomaterial for controlled local release of drugs to the brain for the treatment of TBI. In this research, two silk-based implants, thin silk films and silk-HRP hydrogels, were tested for their ability to consistently deliver small molecules to the brain and subsequently prevent cell and tissue death following a controlled cortical impact mouse model.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: Qiaobing Xu, Barry Trimmer, and Michael Whalen.; Keyword: Biomedical engineering.